PENGARUH PEMBERIAN UBI JALAR UNGU (IPOMOEA BATATAS) TERHADAP PENAMBAHAN BERAT BADAN HAMIL DENGAN KURANG ENERGI KRONIS - Nurul Amalina; Devi Rosima (Universitas Fort de Kock Bukittinggi, 2022)
Pregnant women who experience chronic lack of energy experience protein energy imbalance. Providing additional food, especially for pregnant women with chronic lack of energy, is an effort to overcome nutritional problems, one of which is giving purple sweet potatoes. Data from the Mersip Health Center, the data for 2021 from 77 pregnant who were examined for lila and weight, there were 36 pregnant women with chronic energy deficiency. The purpose of the study was to determine the effect of giving purple sweet potato (ipomoea batatas) to weight gain for pregnant women with chronic energy deficiency in the Mersip ommunity Health Center area. This type of research was a quasi-experimental design, One Group Pretest – Posttest Design. The research was conducted in December 2021. The sample in this study was 15 people. The sampling technique in this research was purposive sampling. Data analysis used Paired Sample T-Test with 95% confidence level. The results showed that the mean weight before being given purple sweet potato was 45.86 and after being given purple sweet potato was 46.81 kg. There was an effect of giving purple sweet potato on weight gain of pregnant women with chronic energy deficiency pvalue 0.0005. It was concluded that there was an effect of giving purple sweet potato on weight gain of pregnant women with chronic energy deficiency. It is expected that mothers always obtain information about the importance of additional food such as purple sweet potato for the prevention of Chronic Energy Deficiency. Keywords: Chronic Energy Deficiency, Purple Sweet Potato, Body Weight